Mapping Alumni Program Studi Manajemen Pendidikan Islam (MPI) Jurusan Tarbiyah STAIN Samarinda - Siti Julaiha (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2015)
Islamic education management study program has 200 alumni. Unfortunely, there was no sufficient information about their jobs and activities after graduating from STAIN Samarinda. The objectiveof this study was to map the alumni of Islamic education management study programof Tarbiyah of STAIN Samarinda. Data were collected by using interview, documentation, and questionnaires. The subject of the study was the alumni of Islamic education management study program who graduated from STAIN Samarinda since 2000 to 2013. Data were analized by using the model of Miles dan Huberman. The findings shows that : firstly, most of the alumni could finish their study in four years. Secondly, the alumni are 51% male and 49% female. Thirdly, regarding to the place of the works, alumni of MPI could be found in Samarinda (majority), Balikpapan, Tenggarong, Bulungan, Sangata, Kota Bangun, Bengalon, Paser, Tanah Grogot, Malinau, Melak, tanah Tidung, and Sangkulirang. Forthly, in terms of the kinds of the jobs, alumni of MPI work in different field of works, such as: teachers, staff administration, and private sectors. Regarding to the aspect of interconectivity between the major and the work field, it could reach 68%.